Предмет: Алгебра,
автор: hgnjh
представьте в виде произведения выражения
1) (3b-5)²-49
2) (a+b-c)²-(a-b+c)²
Ответы
Автор ответа:
0
1) (3b - 5)^2 - 7^2 = (3b - 5 - 7)(3b - 5 + 7) = (3b - 12)(3b + 2) = 3(b - 4)(3b+2)
2) (a + b - c - a + b - c)(a + b - c + a - b + c) = (2b - 2c)2a = 2(b - c)2a =
= 4a(b - c)
2) (a + b - c - a + b - c)(a + b - c + a - b + c) = (2b - 2c)2a = 2(b - c)2a =
= 4a(b - c)
Похожие вопросы
Предмет: Українська мова,
автор: kalynychtanya25
Предмет: Химия,
автор: overgiles
Предмет: Биология,
автор: rinatagabbasova515
Предмет: Математика,
автор: cash982